Liver transplantation for non-alcoholic fatty liver disease—a review - Jayakumar, Saumya (AME Medical Journal; Vol 3 (February 2018): AME Medical Journal, 2018)
Non-alcoholic fatty liver disease (NAFLD) is the leading cause of liver disease in North America, and without any pharmacological treatments readily available for this disease, it is fast emerging as a top indication for liver transplant (LT). Since the main risk factors for the development of fatty liver are the various components of the metabolic syndrome, patients with fatty liver have high rates of cardiovascular (CV) disease and renal dysfunction, both pre- and post-LT. Obesity does not seem to affect transplant outcomes, once the body mass index (BMI) has been adjusted for ascites and edema. However, patients undergoing transplant for fatty liver are at increased risk for cardiac events and sepsis, and their care should be optimized pre-transplant in order to both screen for and optimize cardiac risk factors. The development of fatty liver post-transplant can be separated into two categories: recurrent disease and de novo disease. To date, there are few studies examining the long-term outcomes, but what data does exist suggests that these are two separate entities, with recurrent fatty liver resulting in poorer outcomes, both overall and graft related.